Neurotensin regulation induces overexpression and activation of EGFR in HCC and restores response to erlotinib and sorafenib. (1st March 2017) - Wu, Zherui; Galmiche, Antoine; Liu, Jin; Stadler, Nicolas; Wendum, Dominique; Segal-Bendirdjian, Evelyne; Paradis, Valerie; Forgez, Patricia
Abstract: Hepatocellular carcinoma (HCC) is the third leading cause of death from cancer due to the combination of late diagnosis and a lack of curative treatments. The identification of factors which promote tumor aggressiveness, and those that predict treatment responses, are a means to optimize the management of HCC patients. The complex of Neurotensin (NTS) and its high affinity receptor (NTSR1) has been shown to induce tumor growth and metastasis process in various cancers. In this paper, we propose that NTS and NTSR1 can assist in the management of HCC. Concomitant expression of NTS/NTSR1 was correlated with poor prognosis and found in 50% of HCC patients. We show that NTSR1 expression was positively correlated with the alteration of the Wnt/β-catenin pathway. Its activation creates EGFR driver activation which consequently enhances tumor progression, and sensitizes HCC tumor cells to TKI, such as sorafenib. The NTS/NTSR1 complex is a potential drug target for HCC, because it is an upstream regulator in the chain of cellular events involved in HCC progression. It could also be used as a theranostic biomarker for sorafenib to improve the HCC patient management. Highlights: Neurotensin (NTS) and neurotensin receptor 1 (NTSR1) are indicators of poor prognosis in HCC. NTSR1 expression is associated with Wnt/β-catenin pathway activation. NTS autocrine regulation generates EGFR driver regulation. NTSR1 sustained activation sensitizes HCC cells to TKI. NTSR1 is a theranostic biomarker for sorafenib.